ANALISIS RISIKO OPERASIONAL DALAM PEMILIHAN PERANGKAT KERAS (HARDWARE) DAN PERANGKAT LUNAK (SOFTWARE) PADA INDUSTRI PERBANKAN (Studi Kasus: Bank X) - Ricky Ricky (Jurnal Ekonomi, Manajemen dan Perbankan (Journal of Economics, Management and Banking), 2015)
According to Undang-Undang RI Number 10 Year 1998, Bank is an entity that collects funds from the public in the form of deposits, then channeled to the community in the form of credit or other forms in order to improve the standard of living of the people. Therefore, banks need to make some effort to improve productivity, efficiency, and effectiveness in serving customers. One effort that can be done is by making almost all of the banking operations computerized. Since the computerized operations in the bank is growing, then development and software engineering analysis is needed. The development of software engineering is based on forward chaining expert system analysis against the selection of hardware and software to meet the banking needs. However, the development of software engineering is not only based on the user needs (user requirement) and tools that are used in these process analysis methods, but also the analysis of risk management in each process. By applying risk management in software engineering development process, it can assist the management in decision making (decision support system) for mitigating and minimizing the unexpected risks. The documentation of risk is not only done in the beginning of development, but also when the development is on going, so that it can make the development of software engineering becomes easier